2022
DOI: 10.1200/jco.2022.40.16_suppl.9547
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival (OS) with first-line atezolizumab (A) or placebo (P) in combination with vemurafenib (V) and cobimetinib (C) in BRAFV600 mutation-positive advanced melanoma: Second interim OS analysis of the phase 3 IMspire150 study.

Abstract: 9547 Background: Primary analysis of the phase 3 IMspire150 study (NCT02908672) demonstrated improved investigator-assessed progression-free survival (PFS) with first-line A + V + C vs P + V + C in patients (pts) with BRAFV600 mutation–positive advanced melanoma (hazard ratio [HR] 0.78; 95% CI, 0.63-0.97; P= 0.025). With median follow-up of 18.9 months at primary analysis, OS data were immature; interim analysis of OS at the time of the primary analysis demonstrated a trend in favor of A + V + C over P + V + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Triple therapy in the first line obtained encouraging results in ongoing phase III trials in advanced resectable melanoma. Pembrolizumab + dabrafenib + trametinib improved PFS, duration of response (DOR), and OS compared with placebo + dabrafenib + trametinib ( 29 ), and atezolizumab + vemurafenib + cobimetinib prolonged PFS and provided a clinically meaningful benefit in median DOR compared with placebo + vemurafenib + cobimetinib ( 30 ) in patients with BRAF V600E/K-mutant melanoma. Based on such results, this study will evaluate the neoadjuvant treatment with ICB and targeted therapy followed by adjuvant treatment with atezolizumab (an anti-PD-L1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triple therapy in the first line obtained encouraging results in ongoing phase III trials in advanced resectable melanoma. Pembrolizumab + dabrafenib + trametinib improved PFS, duration of response (DOR), and OS compared with placebo + dabrafenib + trametinib ( 29 ), and atezolizumab + vemurafenib + cobimetinib prolonged PFS and provided a clinically meaningful benefit in median DOR compared with placebo + vemurafenib + cobimetinib ( 30 ) in patients with BRAF V600E/K-mutant melanoma. Based on such results, this study will evaluate the neoadjuvant treatment with ICB and targeted therapy followed by adjuvant treatment with atezolizumab (an anti-PD-L1).…”
Section: Discussionmentioning
confidence: 99%
“…NeoTrio found that concurrent dabrafenib/trametinib/pembrolizumab had higher pCR and pathological response rate compared with dabrafenib/trametinib with sequence pembrolizumab and with pembrolizumab alone, but it had a high toxicity ( 31 ). Our study, differently from NeoTrio study, will use the triple combination with vemurafenib/cobimetinib/atezolizumab which gave positive results in the phase III study in patients with metastatic melanoma ( 18 , 30 ) and is currently approved by FDA. Data from the BRAF wild-type arm of our study will also be useful to understand whether MEK inhibitors have immune-stimulating or immune-suppressor effect in advanced melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Reported Adverse Events Cardiovascular Arrhythmia [21] Cardiac failure [22] Hypertension [23] Myocardial infarction [22] Myocarditis [24,25] Stroke [22] Endocrine Hypothyroidism, hyperthyroidism [26,27] Hypophysitis [28,29] Hyperglycemia [30] Loss of appetite [26,31] Gastrointestinal/renal Colitis/Diarrhea [32] Constipation [26] Esophageal achalasia [33] Hepatitis [34] Nausea [26] Nephritis [35] Pancreatitis [26] General Fatigue [31] Pyrexia [31] Table 1. Cont.…”
Section: Organ Systemmentioning
confidence: 99%
“…Inflammatory myopathy [36] Arthropathy [37] Nervous Encephalopathy [20] Facial palsy [38] Hearing loss, vertigo [39,40] Neuropathy [23] Dermatological Alopecia [23] Dermatitis [14] Rash [26] Pruritus [26] Photosensitivity [26] Vitiligo [26,41] Respiratory Cough [31] Dyspnea [31] Pneumonitis [26] Other Sarcoidosis [42,43] Hematological disturbances Note: common side effects (those affecting between 1 in 10 and 1 in 100 people) are in bold [14,20].…”
Section: Musculoskeletalmentioning
confidence: 99%
“…The OS was not reported due to the short mFU. Updated results from a second interim analysis with a longer mFU did not show any statistical significance with regards to the OS [ 31 ]. Based on these results, triple therapy with atezolizumab, cobimetinib and vemurafenib received FDA approval; this combination is currently the only approved triple therapy.…”
Section: Current Statusmentioning
confidence: 99%